ZAKAT, INFAQ, SHADAQAH, (Kajian Teoritis Dan Praktek Pada Zaman Awal Islam) - Drs. Syahrul (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2016)
Zakat one of the Shari'ah governance seeks to regulate the economy. Pensyariatan zakat has started since the prophet of Allah was in town mecca. More serious attention be given to charity after the Prophet. located in the city of madina in the second year hijriyah, since it is the obligation of zakat in a manner perind rupah sehinggah expected to be able to serve the various needs of a society of. To explain the zakat al-Qur'an uses the term charity, infaq, Sadaqah and haq. According to the language of charity, at least, contain four main meanings: net (al-thuhr). increase (aZ-zn / adaft), grows or (al-nama), thanks to (al-Baraqah) and praise (al-madh). Zakat is a specific part of certain assets issued or disalur-kan in the manner and under certain conditions to persons or entities / agencies that particular way. Zakat should not be delayed because zakat like the poor on the rich when dissidents zakat is the individual, the government authorities have an obligation to force it, whereas if the dissidents were berkelom-pok or group people, then they must be fought until they do so.